(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
It has been estimated that 8-molybdogermanic acid during interaction with Fuchsin basic dye forms the complex associate with four associated cations of dye in the acidity pH 0.9÷1.2; pH 1.7÷2.2; pH 4.0÷5.0. This reaction is distinguished by its high contrasting and sensitivity (ε = 2.5 ·105·L·mol-1· cm-1).